What constitutes good research in e-learning–are there lessons we can draw from the Research Assessment Exercise? - Gráinne Conole (Association for Learning Technology, 2007)
The next Research Assessment Exercise (RAE) is nearly upon us and as such I thought it would be useful to reflect on what the RAE offers us in terms of positioning our own research discipline and how it might help us to answer the question ‘what constitutes good e-learning research?'